Kinetics of gelation in pH/temperature-sensitive hydrogels synthesis - Pinto, Virgínia (2012)
Kinetics of gelation was experimentally and theoretically studied for different polymerization systems leading to the formation of pH/temperature-sensitive hydrogels. Acrylamide (AAm), N-isopropylacrylamide (NIPA), N,Ndimethylacrylamide (DMA), acrylic acid (AA), methacrylic acid (MAA) were used as main monomers, and N,N’- methylenebisacrylamide (MBAm) as crosslinker.